2017
DOI: 10.1016/j.chemosphere.2016.11.131
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Technosol contaminated by former mining activity and its culturable autochthonous microbiota

Abstract: Technosols or technogenic substrates contaminated by potentially toxic elements as a result of iron mining causes not only contamination of the surrounding ecosystem but may also lead to changes of the extent, abundance, structure and activity of soil microbial community. Microbial biomass were significantly inhibited mainly by exceeding limits of potentially toxic metals as arsenic (in the range of 343–511 mg/kg), copper (in the range of 7980–9227 mg/kg), manganese (in the range of 2417–2670 mg/kg), alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Aspergillus and Penicillium strains have been already isolated in several polluted samples ( Chaıneau et al, 1999 ; Da Silva et al, 2003 ; Zafra et al, 2014 ; Al-Hawash et al, 2018 ). Data on soil isolation of Aspergillus niger ( Chaıneau et al, 1999 ) , Aspergillus fumigatus ( Chaıneau et al, 1999 ; Zafra et al, 2014 ), Aspergillus terreus ( Da Silva et al, 2003 ), Aspergillus flavus, Aspergillus niger, Aspergillus nomius ( Zafra et al, 2014 ), Aspergillus sydowii ( Tian et al, 2016 ), Aspergillus versicolor ( Šimonovièová et al, 2017 ) have been reported although few information deals with the here-detected species of Aspergillus (i.e., A. creber, A. jensenii, A. protuberus ). For instance, A. creber and A. jensenii , described as new species in Jurjevic et al (2012) , are mostly known as air-born contaminants or of clinical relevance ( Micheluz et al, 2016 ; Siqueira et al, 2016 ); A. protuberus has been isolated from air and the mussel Mytilus edulis galloprovincialis ( Siqueira et al, 2016 ; Klas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus and Penicillium strains have been already isolated in several polluted samples ( Chaıneau et al, 1999 ; Da Silva et al, 2003 ; Zafra et al, 2014 ; Al-Hawash et al, 2018 ). Data on soil isolation of Aspergillus niger ( Chaıneau et al, 1999 ) , Aspergillus fumigatus ( Chaıneau et al, 1999 ; Zafra et al, 2014 ), Aspergillus terreus ( Da Silva et al, 2003 ), Aspergillus flavus, Aspergillus niger, Aspergillus nomius ( Zafra et al, 2014 ), Aspergillus sydowii ( Tian et al, 2016 ), Aspergillus versicolor ( Šimonovièová et al, 2017 ) have been reported although few information deals with the here-detected species of Aspergillus (i.e., A. creber, A. jensenii, A. protuberus ). For instance, A. creber and A. jensenii , described as new species in Jurjevic et al (2012) , are mostly known as air-born contaminants or of clinical relevance ( Micheluz et al, 2016 ; Siqueira et al, 2016 ); A. protuberus has been isolated from air and the mussel Mytilus edulis galloprovincialis ( Siqueira et al, 2016 ; Klas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other urban environments were not measured for cancer risk comparison in this study. Indeed, pollution can change the environmental microbiome (Simonovicova et al ), therefore, pollution monitoring and amendment will be important in urban microbiome rewilding. Pollution and user activities are potential confounding factors to microbial exposure for health outcomes, and should be controlled for in experiments testing the Microbiome Rewilding Hypothesis.…”
Section: Testing the Microbiome Rewilding Hypothesismentioning
confidence: 99%
“…Microorganisms are a contact group of organisms, which are an important element for successful land reclamation because of their major role in nutrient cycling, plant establishment, biogeochemical transformations of present elements, and soils formation [1], [2], [3]. These are organisms that are highly adaptable to life under the conditions of heavily-burdened areas and extreme stress from the presence of toxic elements [4], [5], [6]. These organisms have an enormous biotechnological potential in the speciation of elements in post-mining substrates, thereby influencing the course of further revitalization of contaminated sites through the biotransformation processes of present toxic metals and semimetals [7], [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%